BioVoice: A multipurpose tool for voice analysis. (February 2021) - Morelli, Maria Sole; Orlandi, Silvia; Manfredi, Claudia
Highlights: BioVoice, a user-friendly software tool for the acoustical analysis of the human voice is presented. BioVoice performs both time and frequency analyses, estimating more than 20 acoustical parameters. Basic parameters are computed as well as new ones specifically developed for newborn cry and singing voice analysis. Examples are presented showing the capabilities of BioVoice also as compared to another existing software tool. Abstract: Objective: This paper introduces BioVoice, a user-friendly software tool for the acoustical analysis of the human voice. It estimates more than 20 acoustical parameters with advanced and robust analysis techniques specifically developed for different vocal emissions, from the newborn to the adult and the singer. Methods: BioVoice performs both time and frequency analyses, detecting the number, length, and percentage of voiced and unvoiced segments and computing fundamental frequency (F0), formant frequencies (F1-F3), noise level, and jitter. The software tool computes the melodic shape of F0 out of 12 basic shapes and allows performing perceptual analysis in newborn and child voice. In the singing voice case, formants up to F5 are computed as well as the quality ratio and parameters concerning vibrato and its regularity. Colour figures and Excel tables show F0, the spectrogram with formants, voiced segments, and quality ratio. Results: Examples of voice analysis in adults, children, newborns, and singers are presented. They show the specific capabilities and the high performance of BioVoice also as compared to another existing software tool. Significance: BioVoice is a free user-friendly software tool for voice analysis that implements new estimation techniques. Basic parameters are computed as well as new ones specifically developed for newborn cry and singing voice analysis, not available with current software tools. Conclusions: BioVoice is capable to deal with low to high pitched voices implementing dedicated tools. Thanks to its simple and intuitive interface, colour figures and Excel tables, it is a valuable tool suitable also for the inexperienced user.